The Implications of Using E-Modules For Improving Teachers' Pedagogic Competence In The International Border of Indonesia-Malaysia - Budiman, Jumardi; Okianna, Okianna; Abdurrahman, Eka Hendry (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: The purpose of this study is to describe the application and implications of the use of PjBL-based teaching modules on the pedagogic competence of the trainee teachers. Methodology: The research method used is a qualitative approach in descriptive form. The research data was obtained by interviewing informants, namely teachers who participated in the training from State High Schools in Beduai, Sekayam and Entikong Districts. Data processing techniques are data reduction, data presentation and conclusion drawn. Main Findings: The results show that the implementation of the use of e-modules in learning in several schools in border areas can provide benefits in improving the quality of learning processes and outcomes, although there are still some challenges in its implementation. The use of e-modules in learning makes a real contribution to efforts to improve teachers' pedagogic competence, especially in the use of technology and the internet in supporting the learning process in the classroom. Novelty/Originality of this study: The researcher intends to test the implications on the pedagogic aspects of teachers who use e-modules as a learning medium in Border Area High Schools in Beduai District, Sekayam District and Entikong District, Sanggau Regency. This sub-district was chosen because it is the outermost sub-district in West Kalimantan, the western region which is directly adjacent to Malaysia.